2020
DOI: 10.24138/jcomss.v16i2.1032
|View full text |Cite
|
Sign up to set email alerts
|

A Speech Quality Classifier based on Tree-CNN Algorithm that Considers Network Degradations

Abstract: Many factors can affect the users’ quality of experience (QoE) in speech communication services. The impairment factors appear due to physical phenomena that occur in the transmission channel of wireless and wired networks. The monitoring of users’ QoE is important for service providers. In this context, a non-intrusive speech quality classifier based on the Tree Convolutional Neural Network (Tree-CNN) is proposed. The Tree-CNN is an adaptive network structure composed of hierarchical CNNs models, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
3
0
1
Order By: Relevance
“…We followed our data processing design just as we explained earlier, before feeding our TBCNN with the blocks of training, validation, and testing. We adopted this model for this research because of how effective it was in [7,23,26] and how they all had a similar problem area, program source code, although with different objectives. The model, which we implemented with kernels, paddings, and slides aside the various layers, performed well with an accuracy of 94% within 10 epochs, as depicted in Figure 8.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We followed our data processing design just as we explained earlier, before feeding our TBCNN with the blocks of training, validation, and testing. We adopted this model for this research because of how effective it was in [7,23,26] and how they all had a similar problem area, program source code, although with different objectives. The model, which we implemented with kernels, paddings, and slides aside the various layers, performed well with an accuracy of 94% within 10 epochs, as depicted in Figure 8.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…To solve this anomaly, we adopted the method of [26] but kept in mind the need to consider semantic and synthetic structures of the software under test (SUT) as proposed by [21]. In Figure 2 below, we present the process flow of our data generation using the µjava tool within MutantBench.…”
Section: Data Generation and Processingmentioning
confidence: 99%
“…In recent years, unsupervised feature learning receives widespread attention in computer vision because automatic learning to obtain robustness’ visual feature expression in the massive unlabeled data (including images and videos) becomes a crucial task for the next generation of intelligent vision applications [ 25 ]. In the ML application, computer vision and neuroscience researchers have reached the consensus shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Feng et al [47] found that acoustic investigations can reveal that impaired speech has a substantially shorter voice start time for aspirated consonants, as well as a smaller vowel spacing. Vieira et al [48] presented a non-intrusive voice-quality classifier based on the tree convolutional neural network for measuring user satisfaction with speech communication platforms. Poncelet et al [49] suggested using an end-to-end spoken language understanding system that can be trained by the user through demonstrations and can translate impaired speech directly into semantics.…”
Section: Assessing Speech-signal Impairmentsmentioning
confidence: 99%